Linearization of multi-objective multi-quadratic 0-1 programming problems - Bhargava, Shifali (International Journal of Advanced Mathematical Sciences, 2014)
A linearization technique is developed for multi-objective multi-quadratic 0-1 programming problems with linear and quadratic constraints to reduce it to multi-objective linear mixed 0-1 programming problems. The method proposed in this paper needs only O (kn) additional continuous variables where k is the number of quadratic constraints and n is the number of initial 0-1 variables. Keywords: Knapsack Constraint, Linearization, Multi-Objective, Multi-Quadratic, Optimal Solution.